Modelling the Public Perception of Urban Public Space Lighting Based on SDGSAT-1 Glimmer Imagery: A Case Study in Beijing, China. (January 2023) - Lin, Zirong; Jiao, Weili; Liu, Huichan; Long, Tengfei; Liu, Yongkun; Wei, Shengrong; He, Guojin; Portnov, Boris A.; Trop, Tamar; Liu, Ming; Li, Xuwen; Wen, Chunhui
Highlights: Establishing the relationship between public perception and light attributes. Using remote sensing data to retrieve residents' perception of public space lighting. Public perception is mainly affected by illuminance, light uniformity and blue light. Mapping public safety and comfort of Beijing with SDGSAT-1 nighttime light imagery. Public perception maps can visually show areas of over- or under-lighting in Beijing. Abstract: Public space lighting is important for public perception, human health and urban planning. Previous studies used nighttime light remote sensing data to evaluate light pollution and its impacts on human health, few investigated the impact on public perception. This study combines Beijing's SDGSAT-1 imagery with ground-measured and public perception data to evaluate the feasibility of SDGSAT-1 images simulating public perception. First, ground measurements were performed to collect light attributes and questionnaires were distributed to assess public safety and comfort. Next, the relationship between SDGSAT-1 image and measured illuminance was established. Lastly, public perception in Beijing was estimated. The results show that, (1) public perception is affected by panoramic illuminance, uniformity, and blue light; (2) although illuminance is positively related to public perception, it shows diminishing marginal returns; (3) a strong correlation is found between panoramic illuminance and SDGSAT-1 image; (4) the perception map shows that most areas in Beijing can provide safe and comfortable lighting, while there are also insufficient or overlit in some places. This study explores methods for assessing public perceptions by satellite data, indicates remote sensing can provide a larger-scale and quantitative evaluation of public perception, which can contribute to urban lighting design and sustainable development.